Paparan bakteri fermentatif pada kualitas nutrisi pakan ternak ruminansia - Syafiradewi Yulianti; Abun; Nyimas Popi Indriani (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2026)
Although feed is a major factor determining the productivity of ruminant livestock, feed, especially green feed, typically has a high fibre content that is difficult to digest effectively, leading to less efficient utilization of nutrients. As a result, efforts are needed to improve feed quality through microorganism-based fermentation, especially fermentative bacteria. The role of fermentative bacteria in improving the nutritional quality of ruminant feed is the subject of this study. The method used is to conduct literature research on relevant national and international journals. The results of the study showed that fermentative bacteria improve feed digestibility, convert lignocellulose into a simpler material, and produce volatile fatty acids (VFA), which are the main source of energy for livestock. Bacterial activity also helps in microbial protein synthesis and nutrient utilization. The type of bacteria, substrate composition, pH, and environmental conditions are some of the factors that affect the fermentation results. As a result, a good idea is to maximize the use of fermentative bacteria to improve the quality and productivity of ruminant animal feed.